Cinnamon (Cinnamomum burmannii) Bark Essential Oil as Raw Material for Skin Cream and Anti-Bacterial - Sandra Lewa; Sanusi Gugule (Acta Chimica Asiana, 2022)
Research has been carried out to identify the essential oil components of cinnamon bark (Cinnamomum burmannii) which will be used in the manufacture of face creams and to test its inhibition against Staphylococcus aureus bacteria. Cinnamon bark essential oil was separated by steam distillation method. The essential oils obtained were identified by gas chromatography-mass spectroscopy (GC-MS) and infrared spectra. The GC-MS chromatogram of cinnamon bark essential oil yielded 3 peaks. The compound that has the largest retention time and concentration is 1,3 octadien-3-ol (linalool). Analysis of absorption data in the infrared spectrum resulted in 3 specific bonds, namely C=O (aldehyde), C=C (aliphatic), and C=N (imin) groups. The results of the formulation and characteristic test of cinnamon bark essential oil cream, all formulations met the National Standard, namely pH 7, adhesion 28.61 seconds, spreadability of 6.1 cm. Inhibition against Staphylococcus aureus was tested using the diffusion method. The greatest inhibitory power was found at a concentration of 15% with a clear zone formed of 2.15 mm.